Correlation Between Blue Light Exposure from Digital Device Screens and Sleep Quality Among Students in the Faculty of Medicine, Universitas Sumatera Utara Class of 2019 - Muhammad Rizki Zaini Lubis; Alfansuri Kadri (Talenta Publisher, 2023)
Background: The use of information and communication technology facilities such as cellphones, laptops, computers, and other information facilities is really needed. From several previous studies it was noted that blue light has an impact on sleep quality, as we already know sleep quality is one of the foundations of health. Objective: The aim is to determine the relationship between blue light exposure on digital device screens and sleep quality, knowing the level of blue light exposure and sleep quality. Methods: This research is an analytical study with a cross-sectional design, namely a type of research in which the measurement of the variables is carried out simultaneously at one time. Results: Of the 150 study subjects, there were 64% women, 36% men. Age, 1.30% were 19 years old, 18.70% were 20 years old, 58% were 21 years old, 20% were 22 years old, 2% were 23 years old. Blue light exposure, bad 94%, good 6%. Sleep quality, bad 87.30%, good 12.70%. The relationship between blue light exposure and sleep quality obtained p-value <0.01 and coefficent r is 0.663. Conclusion: there is significant relationship between blue light exposure on digital screen device and sleep quality of student.